The cowgirl aunt of harriet bean eaudiobook - McCall Smith, Alexander (Harriet Bean, 2015)
Harriet Bean is thrilled! Her two detective aunts Thessalonika and Japonica are taking her across the vast Atlantic Ocean to the wilds of America. When they arrive at their destination, Harriet is happy to discover she has a sixth aunt-Aunt Formica the cowgirl. To add to her joy, Harriet soon learns there's also a mystery to solve. Crafty cattle rustlers are somehow stealing Aunt Formica's cows. But Harriet and her three madcap aunts must move quicker than greased lightning if they want to catch these slippery thieves and save the ranch. It's time to saddle up and follow the clues. ". Alexander McCall Smith [pens] a charming new mystery that will keep young readers guessing-and laughing-from the first clue to the last."-Fantasticfiction.co.uk